The Effect of the Consumer Price Index and GDP on BPRS Assets in Indonesia - Sherli Monika; Muhammad Ikhsan Harahap; Nurul Inayah (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the influence of the Consumer Price Index (CPI) and Gross Domestic Product (GDP) on the assets of Islamic Rural Banks (BPRS) in Indonesia during the 2019–2023 period. Using secondary data obtained from official publications of the Central Statistics Agency (BPS) and the Financial Services Authority (OJK), this research employs a quantitative approach with a causal associative design. After conducting classical assumption tests to confirm the model’s validity, the analysis was performed using multiple linear regression through the EViews 12 software. The research findings indicate that there are no signs of autocorrelation, heteroscedasticity, or multicollinearity, and that the regression model used meets the requirements of normally distributed data. The partial test results (t-test) reveal that the assets of BPRS are not significantly affected by the Consumer Price Index (CPI), but are significantly influenced by the Gross Domestic Product (GDP). The simultaneous test results (F-test) also demonstrate that BPRS assets are significantly affected by both variables simultaneously. These two variables account for 44.03% of the variation in BPRS assets, as indicated by the Adjusted R-Square value of 0.440347; the remaining portion is influenced by factors not included in this research model.